Biological Synthesis of Silver Nanoparticles by Cell-Free Extract of Spirulina platensis - Gaurav Sharma; Nakuleshwar Dut Jasuja; Manoj Kumar; Mohammad Irfan Ali (Journal of Nanotechnology)
The present study explores biological synthesis of silver nanoparticles (AgNPs) using the cell-free extract of Spirulina platensis. Biosynthesised AgNPs were characterised by UV-Vis spectroscopy, SEM, TEM, and FTIR analysis and finally evaluated for antibacterial activity. Extracellular synthesis using aqueous extract of S. platensis showed the formation of well scattered, highly stable, spherical AgNPs with an average size of 30–50 nm. The size and morphology of the nanoparticles were confirmed by SEM and TEM analysis. FTIR and UV-Vis spectra showed that biomolecules, proteins and peptides, are mainly responsible for the formation and stabilisation of AgNPs. Furthermore, the synthesised nanoparticles exhibited high antibacterial activity against pathogenic Gram-negative, that is, Escherichia coli, MTCC-9721; Proteus vulgaris, MTCC-7299; Klebsiella pneumoniae, MTCC-9751, and Gram-positive, that is, Staphylococcus aureus, MTCC-9542; S. epidermidis, MTCC-2639; Bacillus cereus, MTCC-9017, bacteria. The AgNPs had shown maximum zone of inhibition (ZOI) that is 31.3±1.11 in P. vulgaris. Use of such a microalgal system provides a simple, cost-effective alternative template for the biosynthesis of nanomaterials of silver in a large scale that could be of great use in biomedical applications.